(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
One of the most important indicators of the effectiveness of potential anticancer therapies is the decrease in the vitality of cancer cells. An innovative series of cytotoxic 16-(substituted benzylidene) derivatives of dehydroepiandrosterone (DHEA) was synthesised and evaluated for their potential anticancer effects in this work. The MTT test was used for the purpose of synthesis. The MCF-7 cell line, which is used to treat breast cancer, the NCI-H460 cell line, which is used to treat lung cancer, and the SF-268 cell line, which is used to treat cancer of the central nervous system, were all evaluated against a constant concentration of each chemical. The MTT assay demonstrated cytotoxic effects that were dose-dependent, with several substances exhibiting significant reduction of growth. Enhanced tumoricidal efficiency was seen in chemical compounds that included hydrophobic substituents, such as isopropyl and alkyl chains, as well as electron-withdrawing groups, such as nitro and cyano. By boosting the number of receptor interactions, hydroxyl functional groups at carbon (3) and carbon (17) also contributed to an increase in cell bioactivity.